Must Religion be a Conversation-Stopper? - Rosenbaum, Stuart E. (Harvard theological review, 2009)
Richard Rorty has suggested that religion is a conversation-stopper.1 Jeffrey Stout has questioned this claim, gently chiding Rorty for his animus toward increasing assertiveness on the part of religiously committed individuals in their address of public issues.2 Stout concludes that “conversation is the very thing that is not stopped when religious premises are introduced in a political argument.”3 He is convinced that Rorty is overly sensitive on this matter and believes, with Nicholas Wolterstorff and others, that religious people in a pluralistic democracy have not only the right but also the responsibility to share their convictions and the reasoning that leads to their opinions on vital moral and social issues. Stout quotes Wolterstorff as follows: It belongs to the religious convictions of a good many religious people in our society that they ought to base their decisions concerning fundamental issues of justice on their religious convictions. They do not view as an option whether or not to do so. It is their conviction that they ought to strive for wholeness, integrity, integration in their lives: that they ought to allow the Word of God, the teachings of the Torah, the command and example of Jesus, or whatever, to shape their existence as a whole, including, then, their social and political existence. Their religion is not, for them, about something other than their social and political existence; it is also about their social and political existence. Accordingly, to require of them that they not base their decisions and discussions concerning political issues on their religion is to infringe, inequitably, on the free exercise of their religion.4 In what follows, I revisit Stout's question, “is religion a conversation-stopper?” and explain why he believes that Rorty is inappropriately skeptical regarding the role of religion in public life. I then show why Rorty is in fact correct to be skeptical about bringing religious views into discussions of significant public issues.5 Stout, along with Wolterstorff and others, is overly optimistic, and his critique of Rorty reveals his undue optimism. I explain why current perspectives on religion justify Rorty's skepticism about bringing it into public discourse. I also suggest a different perspective on religions that might enable the sort of optimism Stout embraces. The change of perspective I suggest involves taking our religious views not as justified or warranted by documents, sources, traditions, and revelations but rather as embedded in or deriving from those documents, sources, traditions, and revelations. The latter way of understanding our religious views opens them to intellectual strategies of genealogy, or to explanatory strategies that contextualize them within particular traditions of culture and history. I conclude this essay with two relevant points. The first is that neither justifying nor explaining the sources of one's religious views, the strategies roughly of justifying religious beliefs and providing genealogies of them—tools for “deconstructing” them as some would have it—can claim proper priority in our religious lives. Explaining the sources of our commitments is as trenchantly definitive of those commitments as is providing dialectical justification for them. (William James discerns and exploits this fact about our religious views throughout his work.6) My second concluding point is that Stout departs significantly, in ways that adversely affect his views, from the constructive intellectual stances of the classical pragmatists, among whom I include primarily William James and John Dewey; Rorty, although many dislike his views on religion, is a better representative of classical pragmatism than is Stout.